The Premises for Learning Successful Virtual Collaboration in Self-Organizing Teams - Lainema Timo (Igi Global, 2022)
In this study we will introduce a global synchronous e-learning platform that is used for teaching virtual collaboration, multicultural communication, and business process management. The platform has been used in joint learning sessions between international universities and the data of the study has been gathered from self-reflecting essays of the participating university students. We will analyze the data from the point of view of how the students create a social and cultural identity in this totally virtual environment, in which no student will probably ever meet face-to-face his or her team members and collaboration partners. We will consider both the environment as a social construction as well as an environment which is technology supported. In this respect the study has several implications for the educators in the present global and ever technology richer university environment.
E-Learning as a Socio-Cultural System: A Multidimensional Analysis